2017
DOI: 10.1021/jacs.7b03958
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-State-Dependent Binding Properties of the Active Site in a Mo-Containing Formate Dehydrogenase

Abstract: Molybdenum-containing formate dehydrogenase H from Escherichia coli (EcFDH-H) is a powerful model system for studies of the reversible reduction of CO2 to formate. However, the mechanism of FDH catalysis is currently under debate, and whether the primary Mo coordination sphere remains saturated or one of the ligands dissociates to allow direct substrate binding during turnover is disputed. Herein, we describe how oxidation-state-dependent changes at the active site alter its inhibitor binding properties. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
142
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(150 citation statements)
references
References 64 publications
(157 reference statements)
7
142
1
Order By: Relevance
“…Zuschriften previously reported that Mo-FDH requires reductive activation by formate,v iologen, or an artificial reducer to recover its formate oxidation or carbon dioxide reduction activity, although this was not necessary for this Cc-PAA bioelectrode as Mo-FDH is reductively regenerated in situ upon applying areductive potential (i.e., À0.6 Vv s. SHE). [9b, 14,24] Control experiments were performed using Mo-FDH that had been denatured by aerobic heat treatment (100 8 8Cf or 1h), which confirmed that the reductive catalytic wave corresponding to electroenzymatic CO 2 reduction was only observed when active Mo-FDH was used (see the Supporting Information, Figure S1). Thep eak current densities of the denatured Mo-FDH/Cc-PAA control bioelectrode increased slightly,w hich, as described in the introduction, is likely due to changes in the inter-redox moiety spacing in unfolded (denatured) Mo-FDH.…”
Section: Angewandte Chemiementioning
confidence: 65%
“…Zuschriften previously reported that Mo-FDH requires reductive activation by formate,v iologen, or an artificial reducer to recover its formate oxidation or carbon dioxide reduction activity, although this was not necessary for this Cc-PAA bioelectrode as Mo-FDH is reductively regenerated in situ upon applying areductive potential (i.e., À0.6 Vv s. SHE). [9b, 14,24] Control experiments were performed using Mo-FDH that had been denatured by aerobic heat treatment (100 8 8Cf or 1h), which confirmed that the reductive catalytic wave corresponding to electroenzymatic CO 2 reduction was only observed when active Mo-FDH was used (see the Supporting Information, Figure S1). Thep eak current densities of the denatured Mo-FDH/Cc-PAA control bioelectrode increased slightly,w hich, as described in the introduction, is likely due to changes in the inter-redox moiety spacing in unfolded (denatured) Mo-FDH.…”
Section: Angewandte Chemiementioning
confidence: 65%
“…Work by Bassegoda et al 13 and Robinson et al 15 reported the reversible interconversion of CO 2 and formate without using any mediator with the FDH adsorbed on graphite-epoxy rotating disk working electrode. While the direct electrochemical approach adopted by the authors is well-suited to study finer thermodynamic and kinetic properties of metalloenzymes (i.e., FDH), mediated electrochemical approaches facilitated by redox polymers (BPV-LPEI) are better suited for application in devices where increased enzyme loading and current densities can be realized at an electrode surface.…”
Section: -29mentioning
confidence: 99%
“…and Robinson et al 15 showed that Mo-FDH from E.coli adsorbed on the surface of a graphite-epoxy rotating disk working electrode can catalyze the reversible interconversion of CO 2 and formate with direct electron transfer at ∼ −0.4 V vs. SHE (pH 6.8).…”
mentioning
confidence: 99%
See 2 more Smart Citations